Land, people and politics : a history of the land question in the United Kingdom 1878-1952. - Douglas, Roy (London : Allison & Busby, 1976)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: landhervorming; sociale conflicten; Verenigd Koninkrijk